Student Creativity through Project-based Learning Experiences - Desi Desi; Jejem Mujamil; Bety Lesmini; Iceng Hidayat (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to analyze students’ creativity through project-based learning experiences in a electrochemistry topic. Subject of this study was 40 students from Chemistry Education Study Program who took basic chemistry course. Students experienced several activities, namely: forming groups of three, asking and refining questions, debating ideas, making predictions, designing plans and/or experiments, collecting and analyzing data, drawing conclusions, communicating their ideas and findings to others, asking new questions, and creating artifacts like a model, a videotape, or a media. Then, the lecturer monitored the students and the progress of the project, assessed the outcome and evaluated the experience resulting students-in group’ creativity profile. Research instruments are project assessment rubrics and observation sheets. Findings show that students’ creativity in groups ranges from less to very good or from 48.15 to 92.59. Although there are still shortcomings with this study, we encourage other lecturers to implement this type of learning model in other courses or subjects in order to improve students’ problem solving skills.